Deciphering the sensing of alpha-amyrin acetate with hs-DNA: a multipronged biological probe - Pansare, V. Amol; Shedge, Amol A.; Sonawale, Maryappa C.; Pansare, V. Shubham; Mahakal, Akshay D.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Kulal, Dnyaneshwar K.; Patil, Vishwanath R. (RSC Advances, 2022)
In this study, we focus on the biomimetic development of small molecules and their biological sensing with DNA. The binding of herring sperm deoxyribonucleic acid (hs-DNA) with naturally occurring bioactive small molecule alpha-amyrin acetate (alpha-AA), a biomimetic - isolated from the leaves of Ficus (F.) arnottiana is investigated. Collective information from various imaging, spectroscopic and biophysical experiments provides evidence that alpha-AA is a minor groove sensor of hs-DNA and preferentially binds to the A-T-rich regions. Interactions of different concentrations of small molecule alpha-AA with hsDNA were evaluated via various analytical techniques such as UV-Vis, circular dichroism (CD) and fluorescence emission spectroscopy. Fluorescence emission spectroscopy results suggest that alpha-AA decreases the emission level of hsDNA. DNA minor groove sensor Hoechst 33258 and intercalative sensor EB, melting transition analysis (T-M) and viscosity analysis clarified that alpha-AA binds to hs-DNA via a groove site. Biophysical chemistry and molecular docking studies show that hydrophobic interactions play a major role in this binding. The present research deals with a natural product biosynthesis-linked chemical-biology interface sensor as a biological probe for alpha-AA: hs-DNA.